Improving the Odds: Intercostal Metal Coils Mark Area to Resect in Rib Lesions. Issue 4 (July 2017) - Riggs, Kyle W.; Zeltsman, David; Gu, Bo; Sung, Chris C.; Lobko, Igor
Precise localization of a rib lesion for its resection remains a challenge because of multiple factors including nonpalpable pathology, unfavorable body habitus, inaccurate clinical examination, and unreliable rib count on physical examination, unfavorable lesion location within a rib (its posterior aspect), and resection of sclerotic lesions with grossly intact rib cortex. We describe a novel rib localization technique that eliminates potential mistakes and avoids resection of an inappropriate rib. Our method of rib localization includes placement of metallic coils by interventional radiologists under computed tomography guidance where two coils are deployed within the intercostal spaces, one superior and one inferior to the rib lesion. Intraoperative use of fluoroscopy results in precise localization of rib lesions even in cases where the pathology is not grossly apparent. We implemented this approach in 2014 and have since performed it in five patients for both lytic and sclerotic lesions. Placement of markers superficial to the intercostal spaces resulted in their displacement in one case. Successfully, we removed the correct ribs in each patient without technical difficulties or complications. Our series demonstrates a novel strategy for a highly accurate and relatively easy way to identify the exact portion of the rib for surgical resection. Intercostal space positioning of the coil markers superior and inferior to the lesion prevents their dislodgement during patient transport and positioning on the operating room table, which improves rib identification accuracy and reliability. When combined with intraoperative fluoroscopy, it will greatly eliminate resection of incorrect ribs.